2019
DOI: 10.3390/catal9090734
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Catalyzed Glycosylation of Curcumin and Its Analogues by Glycosyltransferases from Bacillus subtilis ATCC 6633

Abstract: Curcumin is a naturally occurring polyphenolic compound that is commonly used in both medicine and food additives, but its low aqueous solubility and poor bioavailability hinder further clinical applications. For assessing the effect of the glycosylation of curcumin on its aqueous solubility, two glycosyltransferase genes (BsGT1 and BsGT2) were cloned from the genome of the strain Bacillus subtilis ATCC 6633 and over-expressed in Escherichia coli. Then, the two glycosyltransferases were purified, and their gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
(43 reference statements)
1
9
0
Order By: Relevance
“…SDS-PAGE analysis showed that the molecular weight of the protein was about 44 kDa (Fig. 1) determined by protein marker, which was the same as our previous verification [9].…”
Section: Expression Purification and Sds-page Analysis Of Bsgt1supporting
confidence: 87%
See 2 more Smart Citations
“…SDS-PAGE analysis showed that the molecular weight of the protein was about 44 kDa (Fig. 1) determined by protein marker, which was the same as our previous verification [9].…”
Section: Expression Purification and Sds-page Analysis Of Bsgt1supporting
confidence: 87%
“…Compared with GTs from plants, microbial GTs generally exhibit remarkable substrate universality [13,14]. Our previous study has proved that BsGT1 from B. subtilis ATCC 6633 had excellent glycosylation ability toward curcumin and analogs [9]. The glycosylation of three chalcone derivatives demonstrated its substrate promiscuity again.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Despite both PPD and PPT skeletons containing the C12 hydroxyl group, ginsenosides with sugar moieties attached to the C12 hydroxyl group have never been identified from Panax species. Compared with plant-derived UGTs, microbial UGTs generally exhibit remarkable aglycone flexibility and poor regiospecificity [13][14][15][16][17][18]. These promiscuous UGTs could be exploited as robust biocatalysts for glycodiversification of natural and unnatural products for new drug discovery [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Other 2-oxindole derivatives are also under clinical trials against various diseases. 3 The incorporation of a sugar moiety in bioactive molecules may have several benefits such has enhancing their bioavailability, 4 their solubility 5 or their biological activity by targeting for example, selectively cancer tissues through the Warburg effect. 6 Such a transformation was achieved in the 2-oxindole series, by chemical synthesis, 7 and recently by biotransformation using Streptomyces sp.…”
mentioning
confidence: 99%